Cytogenetic study in peripheral blood of melanoma patients (2009)
Among all the skin diseases, melanoma is the main cause of death in Colombia (40 %) and it represents 1 % of all deaths by cancer. Due to the fast increase in the incidence of melanoma, it is necessary to carry out research on the mechanisms involved in its genesis and progression. This study determined chromosomal anomalies from peripheral blood samples on 30 patients with melanoma and on 23 control subjects using conventional cytogenetics (G Banded), where a high incidence in numerical anomalies and a low incidence in recurrent structural rearrangements were observed. Chromosomic losses were prevalent in all the tumor stages studied. The analysis showed that the chromosomes X, 9 and 17 were mainly affected. Among the numerical anomalies, monosomies in X and 17 chromosomes, as well as trisomies formed by a marker chromosome, were the most common in both early and late stages of the disease. Deletions and chromosomal crossovers appeared to be as isolated anomalies. In the control group no anomaly was identified, and a low percentage of fragility was observed when compared with the patients group. A high frequency in chromosomal anomalies was observed in patients, in contrast with the control subjects. This suggests the existence of heterogeneity and genetic predisposition during the illness development. To further research, these must be analyzed and validated as possible sources of molecular markers, which could be of use for the early diagnosis, treatment and follow up of the disease.